Mycosis Control of Leafy Vegetables by Chemotherapy - Sahera Nasreen1, Vishal N. Shinde1*, Zafar S. Khan2, and (Journal of Ecobiotechnology, 2011)
In the present study, in vitro potential of three different fungicides like Carbendazim (Systemic fungicide), Mancozeb (Non systemic fungicide) and Captan+Hexaconazole (Mix fungicide) was evaluated against five fungal pathogens of leafy vegetables such as Alternaria brassicae, Collectotrichum lindemuthianum, Fusarium moniliforme, Helminthosporium sativum, Stemphylium verruculosum by Poisoned food technique. Simultaneously the Minimum inhibitory concentration (MIC) of respective fungicides to all five targeted fungal pathogens was also calculated. Out of tested fungicides, Captan+Hexaconazole (Mix fungicide) had marked significant inhibitory effect as it completely inhibited the radial growth averagely 84.33% of all five targeted fungal pathogens in relation to their controls. Whereas remaining, Mancozeb and Carbendazim both were significantly effective and inhibited the radial growth of all targeted fungal pathogens averagely as 60.52% and 54.4%.